Prenatal ultrasound diagnosis of fetal chest wall cystic lymphangioma: An Italian case series. (May 2019) - Saccone, Gabriele; Di Meglio, Lavinia; Di Meglio, Letizia; Zullo, Fabrizio; Locci, Mariavittoria; Zullo, Fulvio; Berghella, Vincenzo; Di Meglio, Aniello
Abstract: Fetal lymphangioma is a rare congenital malformation of lymphatic system that involve the skin and the subcutaneous tissue. The vast majority of the lymphangioma occurs in the neck. More rarely lymphangiomas may occur in the axillary region, including chest wall. Our consecutive case series study included three cases of fetal chest wall cystic lymphangiomas. In our cohort, fetal chest wall cystic lymphangiomas were the 18.8% of the all cases of lymphangiomas of axillary region. In all the three cases no other fetal abnormalities were evaluated, and the chest wall cystic lymphangiomas were unilateral, honeycombed in appearance, with multiple echo-free area of varying size in the mass, with no color flow on Doppler sonography, and with a trend to increase during the gestation. The incidence of chromosomal abnormalities was 33.3%, with one case out of the three being trisomy 21.The literature review revealed only seven cases of fetal chest wall cystic lymphangiomas. The cases were not associated with other abnormalities, nor with abnormal karyotype and only one case of fetal death was reported. Three women delivered vaginally. In summary, fetal chest wall cystic lymphangioma is a very rare malformations with only seven cases reported in the literature. This malformation is usually not associated with abnormal karyotype or other abnormalities and the neonatal outcome is favorable after surgical removal. Spontaneous vaginal delivery may be a safe approach for delivery women with fetal chest wall cystic lymphangioma. Condensation: Fetal chest wall cystic lymphangioma is a very rare malformations with only seven cases reported in the literature. This malformation is usually not associated with abnormal karyotype or other abnormalities and the neonatal outcome is favorable after surgical removal. Spontaneous vaginal delivery may be a safe approach for delivery women with fetal chest wall cystic lymphangioma.